THE ROLE OF TERMS IN LINGUISTICS - Maxmudova Dilafruz Alijonovna (Journals Park Publishing, 2022)
The linguopoetic and linguocultural features of the terms are valuable for the realization of the linguopoetic purpose in connection with the artistic thinking of the creator, and therefore the feasibility of determining the semantic properties of the terms, such as words, in the context of the text is discussed.
Keywords: terms, terminology, artistic text, linvopoetic, linguocultural, metaphor, artistic-aesthetic whole, poetic actualization.